A compact uniplanar antenna for nine‐band LTE/WWAN operation in tablet computers. Issue 6 (23rd March 2016) - Ahmad, Aqsa; Tahir, Farooq A.; Cheema, Hammad M.
ABSTRACT: A compact uniplanar dual wideband antenna for tablet computers is presented. The proposed antenna provides full coverage of LTE700/2300/2500, GSM850/900/1800/1900, UMTS2100, Bluetooth, and 2.4‐GHz WLAN bands with a very small foot print 30 × 10 mm 2 . The antenna has uniplanar structure and is easy to fabricate on single side of 0.8‐mm thick FR4 substrate. This is achieved through three optimized strips: a feeding strip, an inductively coupled inverted L‐shaped strip, and a shorted strip embedded with SMT components. The proposed design supports more than eight operating bands in 3:1 VSWR standard, exhibiting positive gains over all nine bands of operation and 80%–90% radiation efficiency in the higher LTE and WWAN bands. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:496–502, 2016.